Application of ICT in Public Libraries: a Study of Central State Library of Haryana and Chandigarh - Kumar, Parveen (Journal of Information and Knowledge, 2013)
The study of application of ICT in libraries is considered today as the core effect of technology in the changing times. Keeping the above concept in mind a survey has been done in the Central Public Libraries in the northern region of India. The study was conducted to investigate the application of ICT in the Central State Libraries in Haryana and Chandigarh. The study provides to infer that the library automation is one of the effective and efficient application of ICT. The questionnaire comprises various aspects of the selected libraries under study to assess the applications of ICT. The data has been presented in tables along with their interpretation. The findings and a conclusion has been drawn in the light of objectives of the study.